2004
DOI: 10.1111/j.1365-2842.2004.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of colour resulting from composite/compomer layering techniques

Abstract: This study determined the influence of optical properties of constituent layers on the colour of double-layer aesthetic filling materials. Multiple regression equations for the Commission Internationale de I'Eclairage (CIE) L*, a* and b* of layered materials were calculated from the optical values of the covering and underlying layers. Specimens (10 mm diameter, 1 mm thickness) of two light-cured resin composites and one compomer of seven to 11 shades were used. CIE L*, a* and b* values of each specimen were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…A previous study [30] concluded that the optical properties of the cover material generally had a greater influence on color impression of layered samples than those of the underlying material. The influence of the cover layer in the total color perception increased distinctly with the layer thickness.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study [30] concluded that the optical properties of the cover material generally had a greater influence on color impression of layered samples than those of the underlying material. The influence of the cover layer in the total color perception increased distinctly with the layer thickness.…”
Section: Discussionmentioning
confidence: 93%
“…Since Filtek Supreme and Esthet.X composite resins have been developed for clinical usage by multi-layering technique, the resulting restorations in this technique is determined by several factors including translucency, color, and thickness of each layer [1]. Therefore accurate knowledge regarding the translucency and color of materials is fundamental to the layering technique.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding and correct analysis of the optical properties of the natural dentition such as color and translucency and the differences between the natural teeth and restorative materials are very important in accurate and consistent shade selection and the proper use of restorative materials in order to achieve clinical success [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to the optical properties of the material itself, background color and layering effect would influence the final color of a restoration, which was already studied in previous studies. 23,24 These factors should be considered when the results of the present study are applied to clinical situation.…”
Section: Discussionmentioning
confidence: 99%